Hydrogen bond breaking of TPU upon heating: understanding from the viewpoints of molecular movements and enthalpy. Issue 39 (2nd May 2015) - Yuan, Qiang; Zhou, Tao; Li, Lin; Zhang, Jihai; Liu, Xifei; Ke, Xiaolin; Zhang, Aiming
<x xml:space="preserve">Abstract</x> Hydrogen bond breaking of TPU based on 4, 4′-methylenediphenyl diisocyanate (MDI)/1, 4-butanediol (BDO) upon heating was studied and elucidated from molecular movements and enthalpy.